Pandemic Influenza A (N1H1): what to learn from it? - Neumann, Cristina Rolim (2009)
Influenza pandemics are natural events that occur periodically. The pandemic’s current agent, Influenza virus A (H1N1) was first identified in Mexico in April 2009, spread rapidly and has caused deaths mainly among young adults. The objective of this manuscript is to present the biological aspects involved in the outbreak of this pandemic, as well as population-control strategies for pandemic influenza. In addition to the population mitigation measures, whose efficacy has been described by theoretical models, today we also have drugs with efficacy valued in some patient groups. These drugs reduce moderately the duration and severity of symptoms, as long as they are started early. This pandemic, with a large number of cases, but caused by a virus of low lethality, could be managed preferably in Units of Primary Health Care, that would treat the wild cases and forward the severe ones to the hospitals. However, what occurred in numerous cities was the burden on emergency care with triage situations, forcing managers to improvise field hospitals, tents and containers to house the extra work in services that were already at the limit of physical infrastructure and human resources. Pandemic Influenza exposed the fragility of our network of primary care and lack of ICU beds.